Constraints on axionic dark matter in the 3‐3‐1 model. Issue 1 (28th March 2019) - Romero Castellanos, Ana R.; Alvarez‐Salazar, C. E.; Sánchez‐Vega, B. L.
Abstract : Dark matter in the form of axions can be included in models with SU (3) C ⊗ SU (3) L ⊗ U (1) X symmetry with right‐handed neutrinos, where the strong charge‐parity (CP) problem can be solved. Different versions of the model have the appealing characteristic of giving the observed dark matter abundance, measured by the Planck collaboration, for suitable values of the parameters. We studied the constraints on the parameter space of the model obtained when the axion mass is calculated taking into account both quantum chromodynamics (QCD) effects and gravitationally induced operators, making a comparison of three different models.